(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
The article focuses on the theoretical issues of the regional economy, modern problems, ways to solve them, the priority directions of regional development, the need to abandon the practice of centralizing state administration, the need to continue the process of transfer of many powers from the central state bodies to regional bodies and other such topical issues.